PENGEMBANGAN KOMUNIKASI PENDIDIKAN HUMANISME (STUDI DESKRIPTIF PEMBELAJARAN PESERTA DIDIK BIMBINGAN BELAJAR KUMON TINGKAT DASAR DI JAKARTA TIMUR): Pendidikan Humanisme - Sasongko, Yohanes Probo; Rachmad, Teguh Hidayatul (Sintesa, 2024)
The field of education is one of the important things in all human life. In the development of human life, education is an element that cannot be separated from humans. In education, there are many things we can see and pay attention to. In academic terms, we talk about teaching, implementing the curriculum and what things can be considered, as well as things that are developed in education. The process of delivering teaching materials to students, and making students as humans, and not as objects, is one of the priorities that needs to be seen and developed in education. Through education with a humanist approach, the curriculum-based teaching process with its range of achievements becomes something that can be considered in depth. So, we can fully understand the world of education in various aspects and things inherent in it. Therefore, in informal and formal institutions contained in all forms, such as classes, educational curricula and pursuit learning activities summarized therein, they become a form of active learning action and continuous effort to educate humans. With education that elevates and prioritizes human values, every student can become a human being who has the skills, knowledge and ability to express and practice knowledge. Students who are able to develop the knowledge they have. Besides that, with the ability to manage knowledge, itself, in a comprehensive manner, what one obtains in the academic world can be used by oneself in developing one’s life. The Kumon Education Institute in Kali Sari, East Jakarta, is a teaching institution that is oriented towards educating children as students to have great will and desire to overcome their difficulties in learning in various subjects. Therefore, this informal educational institution has established itself as an institution that is beneficial for education in general by positioning itself as a bridge to bring independence to the nation’s future generations. Keywords: Education, Kumon, Humanism, Values, Humans